2021
DOI: 10.1051/ocl/2021033
|View full text |Cite
|
Sign up to set email alerts
|

Root architecture characterization in relation to biomass allocation and biological nitrogen fixation in a collection of European soybean genotypes

Abstract: Soybean [Glycine max (L.) Merr] is the legume with the largest cultivated area worldwide and its yield depends largely on symbiotic nitrogen fixation and root architecture. This study aimed to explore the genetic variability of root architectural traits and di-nitrogen fixing activity in a small collection of nine European cultivars belonging to the same maturity group during their early stages. New image analysis approaches were implemented to characterise root architecture at high throughput. Significant gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…A number of previous studies reported a variability in root traits among soybean cultivars. This variability was observed during early growth (Allmaras et al, 1975;Kaspar et al, 1978Kaspar et al, , 1984Zhao, 2004;Ao et al, 2010;Manavalan et al, 2010;Matsuo et al, 2013;Fenta et al, 2014;Thu et al, 2014;Fried et al, 2018Fried et al, , 2019Mwamlima et al, 2019;Falk et al, 2020;Gao et al, 2020;Dayoub et al, 2021;Maslard et al, 2021), at flowering stage (Zhao et al, 2004;Mwamlima et al, 2019) or at maturity (Ao et al, 2010). Phenotypic differences among soybean cultivars for root traits have been well documented under different conditions (drought, phosphorus availability) across many locations worldwide (Tabs.…”
Section: Genetic Variability For Root Traits In Soybeanmentioning
confidence: 94%
See 4 more Smart Citations
“…A number of previous studies reported a variability in root traits among soybean cultivars. This variability was observed during early growth (Allmaras et al, 1975;Kaspar et al, 1978Kaspar et al, , 1984Zhao, 2004;Ao et al, 2010;Manavalan et al, 2010;Matsuo et al, 2013;Fenta et al, 2014;Thu et al, 2014;Fried et al, 2018Fried et al, , 2019Mwamlima et al, 2019;Falk et al, 2020;Gao et al, 2020;Dayoub et al, 2021;Maslard et al, 2021), at flowering stage (Zhao et al, 2004;Mwamlima et al, 2019) or at maturity (Ao et al, 2010). Phenotypic differences among soybean cultivars for root traits have been well documented under different conditions (drought, phosphorus availability) across many locations worldwide (Tabs.…”
Section: Genetic Variability For Root Traits In Soybeanmentioning
confidence: 94%
“…A wide genetic variability has been reported for most investigated architectural and morphological root traits during early growth (~stage V3) regardless of water regime or soil status. Architectural root traits such as rooting depth, root angle and root width were significantly different among cultivars, irrespective of the water regime and growth environment (Matsuo et al, 2013;Fenta et al, 2014;Falk et al, 2020;Maslard et al, 2021). Root morphological traits as root surface, root volume, taproot length, root tips number and total root length were also different among cultivars (Fenta et al, 2014;Fried et al, 2018Fried et al, , 2019Falk et al, 2020;Dayoub et al, 2021).…”
Section: Genetic Variability In Early Growthmentioning
confidence: 94%
See 3 more Smart Citations